PERANCANGAN SISTEM PENGENDALIAN SUHU DENGAN PENGENDALI PID MENGGUNAKAN ESTIMASI ARX - Khuriati RS, Ainie (BERKALA FISIKA, 2012)
In this paper ARX estimation methodology used to design a PID controller  for  temperature control of the air heater. The step input applied on heating systems and logging the  data   toMATLAB via a data acquisition system. The data obtained is used to identify the model of the processin the form of ARX. PID parameters obtained by minimising a standard  integral errors using theleast squares  method. Then,  the results were compared with the classical methodsKeywords:  PID, Identification,  air heater